Cofactor engineering improved CALB production in Pichia pastoris through heterologous expression of NADH oxidase and adenylate kinase - Jayachandran, Charumathi (PLoS One, 2017)
The cofactor engineering strategy can relieve the metabolic stress induced by expression of recombinant protein in cellular metabolism related to cofactor and energy reactions. To study the effect of cofactor regeneration on recombinant protein expression, NADH oxidase (noxE) was engineered in P. pastoris expressing lipase B (GSCALB). Expression of noxE in P. pastoris (GSCALBNOX) increased NAD(+) levels by 85% with a concomitant reduction in NADH/NAD(+) ratio of 67% compared to GSCALB. The change in the redox level positively influenced the methanol uptake rate and made 34% augment in CALB activity. The decline in NADH level (44%) by noxE expression had lowered the adenylate energy charge (AEC) and ATP level in GSCALBNOX. In order to regenerate ATP in GSCALBNOX, adenylate kinase (ADK1) gene from S. cerevisiae S288c was co—expressed. Expression of ADK1 showed a remarkable increase in AEC and co—expression of both the genes synergistically improved CALB activity. This study shows the importance of maintenance of cellular redox homeostasis and adenylate energy charge during recombinant CALB expression in P. pastoris.